SAT0311 Men and women with psoriatic arthritis express a different genetic profile within the major histocompatibility complex region. (23rd January 2014) - Queiro, R.; Alonso, S.; Tejόn, P.; Fernández, M.; Alperi, M.; Riestra, J.L.; Arboleya, L.; Ballina, J.
Abstract : Background: It has been shown that males with psoriatic arthritis (PsA) tend to suffer from more extended spinal disease while females are more likely to have peripheral joint involvement. It is unclear whether these findings are secondary to differences in occupational physical activity, hormonal changes or other factors (1, 2). Objectives: To investigate whether there are sex-related differences in the genetic profile within the Major Histocompatibility Complex (MHC) among patients with PsA. Methods: One-hundred ten consecutive patients who fulfilled the ClASsification criteria for Psoriatic ARthritis (CASPAR) criteria were randomly selected from the rheumatology outpatient clinic of a tertiary care hospital. There were 55 men and 55 women with a mean age of 48±12 years. The distribution of the following genes and polymorphisms within the MHC region was analyzed according to sex: HLA-DR, TNFA, MICB, MICA, HLA-B, C1_2_5, HLA-C, C1_4_4, OTF3, HCR, CDSN. This typing was also performed in a control population of 110 (55 men and 55 women) random ethnically and geographically matched blood donors. The odds ratio (OR) was calculated by the cross-product ratio and the 95% confidence intervals by the Cornfield method. The extent of linkage disequilibrium between the two loci is expressed as the observed disequilibrium value (λs), i.e., a proportion of the theoretical maximum disequilibrium value (λmax ) achievable for this combination of alleles. The λs were calculated using the formula: λs = λ/λmax = Pab-(Pa.Pb)/Pa.(1-Pb). Results: Compared to PsA males, women tended to have more frequently polyarthritis as the main joint pattern (40% vs. 20%, p<0.05), higher HAQ values (1.10±0.73 vs. 0.72±0.62, p<0.01), and higher swelling joint count (5.2±6.6 vs. 3.4±4.2 p<0.05). HLA-C*06 (56.4% vs. 17%, OR 6.18, 95% CI: 3.32-11.5, p<0.00001), B*27 (31.8% vs. 7.3%. OR 5.9, 95% CI: 2.6-13.4, p=0.0001) and MICA*002 (60% vs. 30%, OR 3.5, 95% CI: 2.0-6.12, p<0.0001) were significantly increased in PsA patients. These three markers were also significantly increased in both sexes. However, HLA-C*07 (49% vs. 25%, OR 2.8, 95%CI: 1.3-6.3; p=0.01) and TNF-308A (45.5% vs. 22%, OR 3.0, 95%CI: 1.3-6.9; p=0.009) were only increased among PsA women. Conclusions: There are gender-related differences in the clinical expression of PsA that might be explained, among other factors, by sex-related differences in the expression of genes and polymorphisms within the MHC region. References: Gladman DD et al. Psoriatic spondyloarthropathy in men and women: a clinical, radiographic, and HLA study. Clin Invest Med. 1992 Aug;15(4):371-5. Queiro R et al. Comparative analysis of psoriatic spondyloarthropathy between men and women. Rheumatol Int. 2001 Oct;21(2):66-8. Disclosure of Interest: None Declared